Climate change mitigation: Low-emission food systems - Castro Nunez, Augusto Carlos (2023)
The mission of Low-emission food systems is to develop and scale research-based solutions that contribute to transforming food and land systems into low emitters of greenhouse gases and delivering sustainable development co-benefits.